Complex Patterns, Unpredictable Consequences: The Distribution of Sealed Land along the Urban-rural Gradient in Barcelona - Ranalli, Flavia; Salvati, Luca (Documents d’Anàlisi Geogràfica, 2015)
The present study explores the spatial pattern of selected soil sealing indicators in the province of Barcelona as a contribution to the debate on land consumption driven by urban growth in southern Europe. Four indicators of soil sealing (percentage of pervious land, per-capita sealed land, soil sealing intensity and diversity in soil sealing intensity) were derived from a high-resolution topographic map at the municipal scale using multivariate statistics and spatial analysis. All the indicators were correlated with the distance from Barcelona. Our results show that sealing patterns in Barcelona reflect distinct urbanization phases observed in the aftermath of World War II and may describe the rapid transition from a mono-centric and compact form observed in the 1950s to a more scattered and dispersed morphology. Soil sealing indicators proved to be effective proxies for the assessment of land-use changes in Mediterranean urban regions.